Developing English Pragmatic Based Material for Students of Hotel Management Study Program - Rahman, Benni Ichsanda; Husnaini, Husnaini (Association of Language Teachers in Southeast Asia (ALTSA), 2018)
There were some miscommunications occurred between speakers and listeners because the listener did not understand the core intent of the speaker, especially what was conveyed implies pragmatic meaning. Thus,